THE DETECTION OF THE NECESSARY CONDITIONS OF EFFECTIVE FUNCTIONING OF THE BALL CLEANING SYSTEM OF THE TUBES OF STEAM TURBINE CONDENSERS. Part 1 - A. G. Gerasimova; A. V. Malgin; Yu. N. Aleksandr; Ye. N. Kriksina (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A problem of an increase of the power of turbine by improving heat transfer in condensers of steam turbines is considered in the article as a topical one. The analysis of contamination of the internal surfaces of cooling tubes and of the influence of pollution on the process of heat transfer in turbine condensers has been fulfilled. The existing method of cleaning of condenser tubes with the use of porous elastic balls of sponge rubber that is implemented on a number of large thermal power plants and state region power plants of the Republic of Belarus is examined. In the operation of the ball cleaning system a significant drawback has been revealed, viz. a low efficiency of this method due to the failure to comply with preparation the system of circulating water for operation. Also, a certain imperfection of ball cleaning system technology has been determined. One of the prerequisites for the effective functioning of the ball cleaning system is a certain degree of purity of the pipe system of the condenser, characterized by the coefficient of purity. To determine the effectiveness of ball cleaning system a series of experiments on the launching of porous rubber balls in the pipe system of the main and the embedded bunches of the T-250/300-240 UTMZ turbine has been produced. Immediately before the experiments hydraulic cleaning of the tubes of the condenser by a high-pressure installation were carried out. During the experiments, records of the number of downloaded porous rubber balls, of the number of rubber balls captured in a loading chamber, and of the number of rubber balls that remained in a calibration device were kept. A large proportion of default of the balls caused by the presence of residues of the carbonate sediments, that obstruct the movement of porous rubber balls in the tubes of the condenser, was determined. The presence of carbonate deposits in the tubes of the condenser indicates a lack of effectiveness of antiscale treatment of circulating water and of hydraulic method of cleaning tubes of the condenser.